Impact of spirituality on physical health (Archives of Clinical Psychiatry, 2007)
BACKGROUND: The implications of spirituality in ones health have been studied and registered in hundreds of articles, demonstrating its relationship with several aspects of physical and mental health,probably positive and possibly causal. OBJECTIVE: To present the recent evidences of the role of spirituality and religiosity in daily clinical practice. METHODS: The articles were selected based on Medline database, through the keywords: "religiosity", "religion", "spiritual" and "spirituality". The articles were evaluated by analysis of method and determination of limitations of studiesdesign. RESULTS: The major findings originated from the association of spirituality, religiosity and immunological activity, mental health, neoplasias, cardiovascular diseases and mortality, besides aspects regarding the intervention of the intercessory prayer, were presented in a descriptive and concise way. CONCLUSIONS: The relationship between the religiosity/spirituality and the physical health has been confirmed but the evidences are not sufficiently conclusive. So, this has become a very promising field of study.